PERSEPSI GURU TENTANG KOMPETENSI MANAJERIAL KEPALA SEKOLAH DI SEKOLAH DASAR NEGERI KECAMATAN PADANG TIMUR KOTA PADANG - Risa Rosalina (Universitas Negeri Padang, 2013)
The goal of this research are to see information about the theachers perception about managerial competency of headmasters. The population is 291 teachers and the sample is 137 people that taken by cluster random sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score and performance level . The result of this research are the teachers perception about managerial competency of headmasters in SD Negeri Kecamatan Padang Timur Kota Padang stay in good enough category. Key word : managerial competency of headmasters